THE ZEN CLOWN IKKYU: A CROSS-CULTURAL STUDY OF A SYMBOL OF DISORDER - Olson, Carl (Journal of Dharma, 1988)
Taking into consideration the rigorous discipline, strict monastc regulations, and arduous daily schedule of a Zen Buddhist monk, it would appear to be self-contradictory to assert that a monk could achieve enlightenment and then faithfully patronize local brothels. It would also appear to be self-contradictory to drink tea in a monastery and sake at a local wineshop, to carry a human skull on a long bamboo pole through the streets and to wander the mountainous terrain of Japan in solitude, and to become head of a leading temple in the twilight years of one's life and, during the same period, to become involved in an illicit love affair. These apparent contradictions characterize the life of lkkvii Sojun (1394-1481), a monk and poet of the Rinzai sect. lkkvu's behaviour was often bizarre, obscene, and outrageous even for an ordinary individual, let alone a zen monk. His appearance, humorous antics, obscene behaviour, and unusual literary compositions closely resemble the nature of a clown.